Thermodynamic Performance of a PTSC-LHTES-ORC-HTHP Hybrid Energy System for Combined Power and Process Heat Production - Güngör, Sercan Gülce (Institute of Electrical and Electronics Engineers Inc., 2026)
This study investigates the design of a hybrid energy system for the simultaneous production of electricity and high-temperature process heat through the combined use of solar energy and industrial waste heat. In this thermodynamically evaluated system, a parabolic trough solar collector (PTSC) was used, and Therminol-VP1 was selected as the heat transfer fluid in the collector. The heat energy obtained from solar energy was stored using latent heat thermal energy storage (LHTES) to make better use of solar energy during cloudy conditions and at night. Additionally, a portion of the heat obtained from solar energy is supplied to the organic Rankine cycle (ORC) evaporator. Industrial waste heat also provides energy to the ORC preheater at this point. In the ORC, n-pentane is used as working fluid. The energy obtained from the ORC turbine is used to drive the compressor of the hightemperature heat pump (HTHP). The heat source for the HTHP is industrial waste heat. R1233zd(E) was selected as the HTHP refrigerant. The Engineering Equation Solver (EES) software was used for the thermodynamic analysis. The analysis results showed that the PTSC and ORC energy efficiency values were 59% and 12%, respectively, while the exergy efficiencies were 16% and 44%, respectively. The HTHP COP value was calculated as 2.9. The energy and exergy efficiency values of the designed system were calculated as 17% and 9%, respectively. The results were deemed promising in terms of their applicability to regions within industrial parks. © 2026 IEEE.
8th Global Power, Energy and Communication Conference, GPECOM 2026 -- 3 June 2026 through 5 June 2026 -- Naples -- 225642
Keywords: High-Temperature Heat Pump; Hybrid Energy System; Latent Heat Thermal Energy Storage; Organic Rankine Cycle; Parabolic Trough Solar Collector